Analisis Metode WASPAS dalam Menentukan Pengangkatan Pegawai Kontrak Menjadi Pegawai Tetap - Abdul Muis; Akbar Idaman; Handry Eldo; Agung Prabowo; Ryan Rinaldi Hadistio; Abdul Muis (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2024)
Human Resources (HR) is a valuable asset for every company, and good management greatly affects operational success. PT XYZ faces challenges in the process of appointing contract employees to permanent employees which is currently done manually, causing a slow and less accurate process. This research aims to develop a method that simplifies and accelerates the process using Weight Aggregated Sum Product Assessment (WASPAS) to simplify and speed up the decision-making process in appointing contract employees to become permanent employees at PT. XYZ, so that decisions taken can be faster, more precise and accurate. This method was chosen for its ability to reduce errors and optimize the assessment with various criteria. The results showed that Alternative 9 was ranked first with a Qi value of 0.9685, showing the best performance among other candidates. The implementation of the WASPAS method is expected to help PT XYZ in making faster, more precise, and accurate decisions, thereby increasing efficiency and objectivity in employee hiring, as well as improving the performance and stability of the company's human resources.